Nahdlatul Ulama in Indonesia, a New Era with the "New Gus Dur" - Nakamura, Mitsuo (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2023)
Islam spread throughout the "Nusantara", one of which was through the missionary work of Wali Songo and other clerics, who accepted, inserted and integrated Islamic teachings with the original pre-existing culture which was then known as "Islam Nusantara" which was characterized by moderation, justice, progress, middle ground and harmony. Nahdlatul Ulama (NU) can be classify as the largest Islamic organization worldwide, with around 121 million members. NU upholds Pancasila and the unity of diversity, namely religious and cultural pluralism. This is the line of indigenization and Indonesianization of Islam that was propagated by Gus Dur. Gus Yahya's new leadership acknowledged as able to absorb Gus Dur's ideology of tolerance, openness, the middle way, gradualism, pluralism, humanity, and the flexible application of Islamic law (fiqh). Gus Yahya was also able to take charge of Abdurrahman's controversial visit to Israel and has toured to promote dialogue between the two sides. Israelis and Palestinians, believe that "reconciliation and coexistence between them" is one of the keys to peace. That is the reason why Gus Yahya is called as the reincarnation of Gus Dur. The new leadership aims to strengthen NU's vitality and independence as an organization. Improving management capabilities and improving the standard of living of the NU support base, namely farmers and fishermen, as well as increasing the micro, small and medium enterprises, trade, and industry. All NU members are expected to act as social reform promoters (agents of change). The composition of the new leadership proofed as fully rich in diversity, including the appointment of women leaders, local activists, young intellectuals, influential Habib (descendants of the Prophet Muhammad), and Chinese Muslims. In particular, the inclusion of 11 women in the central leadership was a milestone for NU.